Foldable single bed - Mohd Kamil, Ramli (2009)
This report presents about bed that always been used especially in bedroom has a small space. This bed is a device which is important in order to ease keep any closet and to save the space. The idea of the fabricating of this bed is based on student's creativity. The selection of suitable materials in the fabricating of this bed is a loaded material which has minimum weight, long life-span and can detain heavy load. Materials are proposed for the fabrication of the bed is mild steel material. In this report, we'll . also be more to the fabrication 'of this bed. There are several processes involved during the design and fabrication of this foldable single •bed which are consisted in this report. Variety of process used in making this .bed as material selection, cutting, joining, and others.